Proposed upgrading to existing interior design of Planetarium Negara at no.53, Jalan Perdana, 50480 Kuala Lumpur for National Space Agency (ANGKASA) / Mohd Asyrani Rosani - Rosani, Mohd Asyrani (2012)
The aim of this research is to identify the problems and find solutions for the proposed upgrade to the existing National Planetarium as the management at the National Planetarium are planning to upgrade their exhibitions and facilities. Another objective of this research is to organize the information obtained from the research done and extract information that will help in solving problems identified. This report also will serve as documentation to ensure the design process will stay on the right path. Both qualitative and quantitative methodologies are used in the process of this research. The qualitative research data is obtained from interviews with the workers of the National Planetarium and the visitors. This method is also used during the case study at Petrosains, Kuala Lumpur, and National Science Centre, Kuala Lumpur. The quantitative research data was gathered with the aid of questionnaires. The result of preliminary observation revealed that there is a need to upgrade the exhibition due to the high level of visitors that are not satisfied on the exhibits inside the National Planetarium. The designer recommends that the National Planetarium undergoes a full upgrade especially in terms of their exhibitions to coincide with the future plan of the National Planetarium. This project is done to help the management of the National Planetarium get an overview of what will the upgrade would look like. Based on the observation done the current issue that is are mainly lacking a good flow for the visitor to look at the exhibit and go around the gallery, and in addition of little improvement over the years. Due to this the designer recommends a complete overhaul of the exhibitions and to create a more interactive exhibits and better attraction. A better flow is introduced to enhance the visitors experience and to give more comfort. It is intended that this complex will be the centre for all other Planetarium in Malaysia to refer to, and to be the centre of space and technology learning.